Legal Representation of Unaccompanied Minors: An Assessment in Terms of Türkiye and Selected European Countries - Hümeyra Zeynep Nalçacıoğlu Erden (Public and Private International Law Bulletin)
The legal representation of unaccompanied minors who are not being cared for by their parents or any other adult stands out as one of the main global problems. These children are under no one’s custody and need representatives who will represent them in all legal proceedings, especially during the asylum process, who will take primary responsibility for their shelter, education, and development, and who will ensure that decisions regarding the child are applied in accordance with the child’s best interests. In line with states’ obligations arising from the Convention on the Rights of the Child, they are responsible for resolving the legal representation of unaccompanied children either by helping children adapt to the current national legislation or by enacting new regulations specific to unaccompanied minors. The legal representation of unaccompanied minors, whose number is also increasing in Türkiye, is mainly carried out within the framework of the Turkish Civil Code and the Child Protection Law. This study will examine the legal representation of unaccompanied minors in Türkiye through examples given from current legislation and practice, including those in selected European countries, and will present recommended solutions.